Financing technology-based small firms in Europe: A review of the empirical evidence - Valérie Revest; Sandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
This paper reviews the evidence on financing technology-based small firms (TBSFs) in Europe. The main findings in the literature are the 1) European TBSF's finance new investments by relying primarily on internal funds, due to capital market failures induced by asymmetric information; 2) European venture capital has caught up with US venture capital, but this ist mainly because of the growth in UK venture investments, and it is unclear whether European venture capital has been able to certify the quality and to enhance the growth of funded companies; 3) the development of trading in high-technology stocks has been limited, if compared with the NASDAQ: the so-called New Markets established in the Nineties have collapsed in the wake of the Internet bubble crash; 4) public venture capital and R&D tax incentives have positively affected high-tech firms, but more research is needed on the forms of public support and on their evaluation.
Keywords: G24; G28; G32; M13; 330; technology-based small firms; capital structure; venture capital; high-tech stock markets; public support